Hidden surface microstructures on Carboniferous insect Brodioptera sinensis (Megasecoptera) enlighten functional morphology and sensorial perception - Prokop, Jakub; Pecharová, Martina; Ren, Dong (Scientific reports, 2016)
Megasecoptera are insects with haustellate mouthparts and petiolate wings closely related to Palaeodictyoptera and one of the few insect groups that didn't survive the Permian-Triassic mass extinction. Recent discovery of Brodioptera sinensis in early Pennsylvanian deposits at Xiaheyan in northern China has increased our knowledge of its external morphology using conventional optical stereomicroscopy. Environmental scanning electron microscopy (ESEM) of structures, such as antennae, mouthparts, wing surfaces, external copulatory organs and cerci have shed light on their micromorphology and supposed function. A comparative study has shown an unexpected dense pattern of setae on the wing membrane of B. sinensis. In addition, unlike the results obtained by stereomicroscopy it revealed that the male and female external genitalia clearly differ in their fine structure and setation. Therefore, the present study resulted in a closer examination of the microstructure and function of previously poorly studied parts of the body of Paleozoic insects and a comparison with homologous structures occurring in other Palaeodictyopteroida, Odonatoptera and Ephemerida. This indicates, that the role and presumptive function of these integumental protuberances is likely to have been a sensory one in the coordination of mouthparts and manipulation of stylets, escape from predators, enhancement of aerodynamic properties and copulatory behaviour.
Keywords: Insecta; Microscopy, Electrochemical, Scanning; zkameněliny; Male; Animals; Fossils; Female; mužské pohlaví; ženské pohlaví; skenovací elektrochemická mikroskopie; hmyz; zvířata; Animal Structures; anatomické struktury zvířat